(untitled) (Research, Society and Development, 2021)
The World Health Organization reports that the majority of the world’s population will live to be 60 years or more. In order to have a longer life, with quality of life, the health factor is essential. Consequently, having access to clear and reliable information about the diseases you live with is an important tool for the prevention and treatment of diseases. Thus, the objective was to research, through the application of a questionnaire, the theme of choice, by the clientele, for the action of conversation circles in a public clinic, and to verify whether contact with the disease influences the interest in the search for knowledge about the same. The experience took place in the waiting room of the Sette de Barros Ambulatory, after Ethics approval - opinion 2,925,286. The printed questionnaire was applied to 378 people, in the months of September and November 2018. The survey identified that: (i) regarding the topics chosen for discussion, the most voted was depression with 292 votes; followed by arterial hypertension (261); dyslipidemia (256) and insomnia 247; (ii) most respondents demonstrated having contact with someone who has hypertension (311 respondents), followed by depression (291 opters), insomnia (289) and diabetes (287). It is inferred that there is a positive relationship between the choice for the topic and the experience of patients with the diseases, since it is more recurrent that individuals have doubts about the topic and Primary Care is one of the places to search for safe information and accessible on health-related topics.